Validation of a Brazilian Portuguese Version of the Walking Estimated-Limitation Calculated by History (WELCH) - Cucato,Gabriel Grizzo (2016)
Abstract Background: The Walking Estimated-Limitation Calculated by History (WELCH) questionnaire has been proposed to evaluate walking impairment in patients with intermittent claudication (IC), presenting satisfactory psychometric properties. However, a Brazilian Portuguese version of the questionnaire is unavailable, limiting its application in Brazilian patients. Objective: To analyze the psychometric properties of a translated Brazilian Portuguese version of the WELCH in Brazilian patients with IC. Methods: Eighty-four patients with IC participated in the study. After translation and back-translation, carried out by two independent translators, the concurrent validity of the WELCH was analyzed by correlating the questionnaire scores with the walking capacity assessed with the Gardner treadmill test. To determine the reliability of the WELCH, internal consistency and test–retest reliability with a seven-day interval between the two questionnaire applications were calculated. Results: There were significant correlations between the WELCH score and the claudication onset distance (r = 0.64, p = 0.01) and total walking distance (r = 0.61, p = 0.01). The internal consistency was 0.84 and the intraclass correlation coefficient between questionnaire evaluations was 0.84. There were no differences in WELCH scores between the two questionnaire applications. Conclusion: The Brazilian Portuguese version of the WELCH presents adequate validity and reliability indicators, which support its application to Brazilian patients with IC.